Sphincter of Oddi Dysfunction and the Formation of Adult Choledochal Cyst Following Cholecystectomy: A Retrospective Cohort Study. Issue 47 (November 2015) - Xia, Hong-Tian; Wang, Jing; Yang, Tao; Liang, Bin; Zeng, Jian-Ping; Dong, Jia-Hong
Abstract : Abstract: To determine the causes underlying the formation of adult choledochal cyst. Anomalous pancreaticobiliary junction is the most widely accepted theory regarding the etiology of choledochal cyst. However, choledochal cysts have been found in patients in the absence of this anomaly. Because the number of adult patients with choledochal cyst is increasing, it is important to address this controversy. Bile amylase levels in the cysts of 27 patients (8 males and 19 females) who had undergone cholecystectomy were retrospectively evaluated. The average age of the 27 patients was 45.8 ± 10.1 years and the majority (85.2%) were diagnosed with Todani type I cysts. None of the patients had dilatation of the common bile duct prior to surgery. There were 6 (22.2%) patients with anomalous pancreaticobiliary junction. However, amylase levels did not significantly differ between patients with and without this anomaly ( P = 0.251). According to bile amylase levels, pancreatobiliary reflux was present in 21 (77.8%) patients. The mean amylase level significantly differed in patients with pancreatobiliary reflux (23, 462 ± 11, 510 IU/L) and those without (235 ± 103 IU/L) ( P < 0.001). In patients with pancreatobiliary reflux, only 4 patients had anomalous pancreaticobiliary junction. That is, the majority of patients (17/21, 81%) having pancreatobiliary reflux did not have an anomalous junction of the pancreatic and biliary ducts. Since the only explanation for pancreatobiliary reflux in patients with a normal pancreaticobiliary junction is sphincter of Oddi dysfunction, we proposed that the formation of adult choledochal cyst is mainly due to sphincter of Oddi dysfunction.